Solid‐state fermentation produces greater stearidonic acid levels in genetically engineered Mucor circinelloides. (1st December 2022) - Xin, F.; Wang, R.; Chang, Y.; Xie, Z.; Zhao, Y.; Zhang, H.; Song, Y.
Abstract: Omega‐3 (ω‐3) polyunsaturated fatty acids (PUFAs) are important dietary components due to their health benefits and preventative role in cardiovascular disease. Fish‐based and plant seed oils are rich in stearidonic acid (SDA; 18:4, n‐3), which are readily metabolized into ω‐3 PUFAs such as eicosapentaenoic acid. However, these natural sources of SDA are generally low yielding and are unlikely to meet global demands, so new sustainable microbial fermentative sources of SDA need to be identified. Expression of delta15‐desaturase in the oleaginous filamentous fungus Mucor circinelloides (McD15D) has been used to construct a recombinant SDA‐producing McD15D strain that produces 5·0% SDA levels using submerged fermentation conditions. Switching to solid‐state fermentation conditions in the same medium with submerged fermentation resulted in this engineered strain producing significantly higher amounts of SDA. A Box–Behnken design of response surface methodology approach has been used to identify optimal glucose and ammonium tartrate concentrations and temperature levels to maximize SDA production. The use of these optimal solid‐state fermentation conditions resulted in the spores and mycelium of the recombinant McD15D producing 19·5% (0·64 mg g −1 ) and 12·2% (1·52 mg g −1 ) SDA content, respectively, which represents an overall increase in SDA yield of 188·0% compared with SDA yields produced using submerged fermentation conditions. Abstract: Significance and Impact of the Study: Solid‐state fermentation is an efficient and economical method for lipid accumulation in the oleaginous microorganism. In this study, engineered strains Mucor circinelloides McD15D with overexpressing the delta15‐desaturase were able to accumulate more stearidonic acid (SDA) under solid‐state fermentation than submerged fermentation, providing a new strategy for fermentation technology to enhance SDA production by oleaginous microorganisms.